Prediksi Farmakokinetik, Toksisitas, dan Aktivitas Enzim Protease HIV-1 Inhibitor dari Daun J. gendarussa - Widodo, Agustinus (Jurnal Farmasi Sains dan Terapan, 2019)
Justicia gendarussa Burm.f. (Acanthaceae) has been known to have anti-HIV activity. This study was conducted to determine the interaction of flavonoids (gendarusin A, B, C, D, and E) on the J. gendarussa leaves against HIV-1 protease receptor. It is expected that this research will provide scientific information on the development of J. gendarussa leaves as an anti-HIV drug. This study used in silico testing methods with FAF-Drugs4 to predict the ADMET (absorption, distribution, metabolism, and excretion–toxicity), and Molegro Virtual Docker (MVD) to predict the activity of five gendarusin compounds to the receptor of HIV-1 protease (PDB ID: 4HLA). The activity prediction was reflected by hydrogen bond and steric bond visible in MVD program with amino acid residue of the receptor of HIV-1 protease. Gendarusin compounds had good oral bioavailability and were not toxic, and from molecular docking test, it was found that gendarusin of J. gendarussa leaves could inhibit the activity of HIV protease enzyme. Gendarusin of J. gendarussa has potential as an anti-HIV.